KUALIFIKASI PELAYANAN PUBLIK YANG BERKUALITAS DALAM UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK - Mayasari, Novita; Ahmidi, Ahmidi; Alhamdani, Alhamdani; Azzahra, Atiqah Amalya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This article aims to provide a qualification of quality public services, so that it becomes a reference for government agencies engaged in the public sector. The Ombudsman has compiled an assessment of public administration compliance, the results show that 10.92% or 64 public services at the ministry, agency and local government level are of low quality. Based on this, this article focuses on analyzing the qualifications of quality public services based on Law Number 25 of 2009 concerning Public Services. The results of this study indicate that, regarding the qualifications of quality public services are contained in the Implementation Behavior in Service Article 34 of Law No. 25 of 2009, which states that public servants must behave fairly and non-discriminatory, careful, polite and friendly, firm, reliable and responsible to the community as service recipients. The method used in this research is normative juridical method based on secondary, primary and tertiary legal materials collected through literature study